2018
DOI: 10.21815/jde.018.078
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of Dental Patient Attitudes on the Likelihood and Perceived Importance of Disclosing Daily Medications

Abstract: An accurate medication history allows the oral health care provider (OHCP) to evaluate a patient's overall health and disease status, as well as assess the effect medications may have on dental treatment and oral health. It has been previously documented that dental patients do not always report an accurate medication list. The aims of this study were to determine dental patients' perceptions regarding the importance and likelihood of accurately disclosing prescription, over-the-counter (OTC), and herbal/suppl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 39 publications
1
5
0
Order By: Relevance
“…Our findings align with previous work examining the process of medication reconciliation in ambulatory care settings [ 14 , 15 , 21 ]. For example, Heyworth et al in semi-structured interviews with healthcare providers also found that while providers recognized the importance of medication reconciliation, they also noted barriers such as the lack of a standardized process and training, patients’ lack of knowledge, lack of time, and the challenges associated with communication between sites of care and utilizing the EHR for medication reconciliation [ 14 ].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Our findings align with previous work examining the process of medication reconciliation in ambulatory care settings [ 14 , 15 , 21 ]. For example, Heyworth et al in semi-structured interviews with healthcare providers also found that while providers recognized the importance of medication reconciliation, they also noted barriers such as the lack of a standardized process and training, patients’ lack of knowledge, lack of time, and the challenges associated with communication between sites of care and utilizing the EHR for medication reconciliation [ 14 ].…”
Section: Discussionsupporting
confidence: 90%
“…We queried our EHR for all patients at least 18 years of age, seen at one of the primary care clinics at Geisinger for a visit with their primary care provider in the past three months prior to the administration of the survey, had at least one medication on their profile, and had an e-mail address on file. The survey was informed by the observations, staff interviews, and existing literature (Appendix D in S1 File ) [ 15 , 21 ]. The survey was 19 questions and based on pilot testing, completion should have taken no more than 15 minutes.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also possible that the patient may not disclose to the dentist that he or she is taking oral nutritional supplementation, because they may not consider it necessary, or even consider an Oral Nutritional Supplements as medication. This is indeed a grey area; for example, the British National Formulary categorises Oral Nutritional Supplements as “borderline substances” or a “food that has characteristics of drugs” 31 . A survey of patients presenting at a US dental school showed that while over 80% of patients surveyed “always informed” their dentist about the prescription drugs they took, only 63% informed them about supplements they took, and 14% thought it was “unimportant” to tell their GDP about supplements 32 .…”
Section: Dental Implicationsmentioning
confidence: 99%
“…Thus, with this issue, we are introducing a new section: Dental Patients and Practice. Our first article in this section reports on a study, conducted by a team of dental and pharmacy faculty, of dental patients’ attitudes about disclosing their daily medications to their oral health care provider 1 . Previously published articles that we forced into existing sections at the time, but would fit more appropriately in this new section include those that addressed dental practitioners’ implementation of tobacco cessation with their patients, 2 racial/ethnic minority older adults’ perspectives on oral health care, 3 and dentists’ role in teaching hospitals in Brazil 4 …”
mentioning
confidence: 99%